Estudo da associação entre transtornos de personalidade e alterações de neuroimagem em pacientes com epilepsia mioclônica juvenil - Araujo Filho, Gerardo Maria de [UNIFESP] (2009)
Purpose: Studies involving juvenile myoclonic epilepsy (JME) patients have demonstrated an elevated prevalence of cluster B personality disorders (PD) characterized as emotional instability and immaturity, unsteadiness, lack of discipline, hedonism, frequent and rapid mood changes and indifference towards their disease. In the present study we aimed to verify a possible correlation between structural and functional brain abnormalities in magnetic resonance image (MRI) and the presence of PD in JME using the techniques of voxel-based morphometry (VBM) and magnetic resonance spectroscopy (MRS). Methods: Sixteen JME patients with cluster B PD, 41 JME patients without any psychiatric disorder and 30 healthy controls were submitted to a psychiatric evaluation through SCID-I and SCID-II and to a MRI. The techniques of voxel-based morphometry (VBM) and quantitative multivoxel magnetic resonance spectroscopy (MRS) were performed. Groups were paired according to age, gender and manual dominance. Results: In VBM study, reduction of gray matter volume (GMV) in right thalamus and increase of GMV in right and left mesiofrontal and in right frontobasal areas were observed in JME patients with PD, while in MRS there was reduction of NAA/Cr ratio in right thalamus and in mesiofrontal regions bilaterally in the group of JME with PD. In addition, a significant increase of GLX/Cr ratio was also observed in mesiofrontal regions bilaterally in the same group of patients. Conclusions: The thalamus, mesiofrontal and frontobasal regions are involved in the pathophysiology of JME and cluster B PD. These data support the hypothesis that PD in JME could represent more intense frontal lobe dysfunctions and possibly a more severe form of this epileptic syndrome.